Removal of vanadium from aquatic environment using phosphoric acid modified rice straw. Issue 1 (2nd January 2020) - He, Wen-yan; Liao, Wei; Yang, Jin-yan; Jeyakumar, Paramsothy; Anderson, Christopher
Abstract: Vanadium (V) is a toxic metal, which dominantly exists as V 5+ in an aquatic environment. Rice straw, which is an abundant agricultural by-product throughout China was used to treat V 5+ containing wastewater as an adsorbent after phosphoric acid treatment. The effects of initial V 5+ concentration, solution temperature, pH and reaction time on V removal by phosphoric acid modified rice straw (AcM) were systematically assessed. A pH range of 2.0–3.0 was favorable for V removal and the adsorption capacity of V by AcM increased with elevated solution temperature. The maximum adsorption capacity for water containing 500 mg V 5+ L −1 was 24.70 mg V g −1 dry matter under the optimum operation (3.33 g L −1 AcM, pH = 2.0, 50 °C, and 200 rpm for 4 h). Adsorption experiment data fitted well to pseudo-second-order kinetic and Langmuir adsorption isotherm models. In the presence of coexisting ions, Na +, Cu 2+, NO3 − and Cl − had no significant ( P > 0.05) effect on V removal. These results indicated that AcM derived from agricultural waste was effective to remove V 5+ from aqueous solution.